FENOMENA PENGGUNAAN MEDIA SOSIAL DAN PENGARUH TEMAN SEBAYA PADA GENERASI MILENIAL TERHADAP KEPUTUSAN PEMBELIAN - Wikan Wiridjati; Renny Risqiani Roesman (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this study is to expand research on purchasing decisions by millennial generation. For this purpose, this study empirically examines the influence of social media and peer influence directly on the purchase decision and indirectly through electronic word-of-mouth. The purposive sampling technique was used, the object of this research involves millennial generation with age criteria between 18 years to 35 years. The research is done by spreading questionnaires to 300 people with 75% respond rates. Structural equation modeling was used to examine the proposed model. Social media usage and peer influence have positive impact on purchase decision involvement and electronic word of mouth plays vital mediating role in this context. The result shows there is no significant effects from peer influence to the purchase decision, but there is significant effects from social media usage and electronic word of mouth. The most significant is coming from the electronic word of mouth. Engaging millennial generation consumers with social media campaigns and mobile technology development, such as Facebook ads, pages like ads, or ads on youtube can increase the value of purchasing decisions. Marketers need to pay attention to the mixed effects of using social media and eWOM.